Analysis Of The Effect Of Leadership And Work Attitude On Employee Work Productivity At The Office Of Cooperatives And Small Medium Businesses East Oku Regency - Winda feriyana; Sri Sarwo Sari; Oliyah Firasati (International Journal of Artificial Intelligence Research, 2022)
This study aims to analyze partially or jointly Leadership, Work Atmosphere on employee work productivity and analyze the most dominant variables in influencing employee productivity at the East OKU Regency Cooperatives and Small and Medium Enterprises Office, the results of regression analysis and the correlation between leadership and work productivity. employees show the regression model = 26,338 + 0.586X1 + e with a correlation coefficient of 0.691. The results of the regression analysis and the correlation between work atmosphere and employee productivity show the regression model = 0.571 + 0.908X2 + e with a correlation coefficient of 0.931. The results of multiple regression analysis and the correlation between leadership and work atmosphere together on work productivity show the regression model = 2.676 + 0.115X1 + 0.821X2 + e with a correlation coefficient of 0.936. This research was conducted on 33 respondents with the analytical method used is path analysis using SPSS software.